Exploring the role of social media credentials in mobile learning: The engagement perspective - Katuk, Norliza (2015)
This paper presents a study on social media credentials as an authentication mechanism for accessing a mobile learning application.The aim of the study is to investigate whether the use of social network credentials would have effect on mobile learning activities particularly learners’ engagement.An experimental study was conducted on forty students from a higher learning institution in Malaysia using a mobile learning application named LANGKAWI APPS and a learning engagement questionnaire.The mobile application was developed in two versions, one with the social network login facility and the other one with traditional authentication method.The results of the statistical tests demonstrate that social network credentials was rated higher by the learners in terms of attention in mobile learning compared to the traditional method.The results are discussed in terms of applicability of social network credential as an authentication mechanism for mobile learning.